PENGARUH LAYANAN INFORMASI FORMAT KLASIKAL DENGAN TEKNIK DISKUSI TERHADAP MINAT SISWA MELANJUTKAN KE SEKOLAH MENENGAH KEJURUAN PADA SISWA KELAS IX SMP NEGERI 22 KOTA BENGKULU - Maya Dwi Kurnia; Sri Saparahayuningsih; Arsyadani Mishbahuddin (UNIVERSITAS BENGKULU, 2024)
This study aims to determine the effect of classical format information services with discussion techniques on students' interest in continuing to vocational high schools in class IX students of SMP Negeri 22 Bengkulu City, this research uses the experimental method of one group pretest-posttest design. The population in this study were ninth grade students of SMP Negeri 22 Bengkulu City, totaling 60 students. The sample was taken using simple random sampling technique which amounted to 30 students. The research data analysis technique used the T test(paired sample test) with Bungin's formula. The results of the study before being given services with an average of 90.27 which is categorized as low. After being given the service the average value of students with a score of 133.77 which is categorized as high. Hypothesis testing in the study was shown with a value of t -22.494 which means that there is an effect of classical format information services with discussion techniques on students' interest in continuing to vocational high schools. From the results of the research, it is suggested that counseling teachers can use a classical format information service model to increase students' interest in continuing their education to vocational schools. Keywords: Interest in Continuing to Vocational High School, Information Services, Classical Format, Discussion Techniques